Orexins Activates Protein Kinase C-Mediated Ca2+ Signaling in Isolated Rat Primary Sensory Neurons - Ozcan, M.; Ayar, A.; Serhatlioglu, I.; Alcin, E.; Sahin, Z.; Kelestimur, H. (Acad Sciences Czech Republic, Inst Physiology, 2010)
Previous results have suggested that orexins causes a rise of intracellular free calcium ([Ca2+](1)) in cultured rat dorsal root ganglion (DRG) neurons, implicating a role in nociception, but the underlying mechanism is unknown. Hence, the aim of the present study was to investigate whether the orexins-mediated signaling involves the PKC pathways in these sensory neurons. Cultured DRG neurons were loaded with 1 mu mol Fura-2 AM and [Ca2+](l); responses were quantified by the changes in 340/380 ratio using fluorescence imaging system. The orexin-1 receptor antagonist SB-334867-A (1 mu M) inhibited the calcium responses to orexin-A and orexin-B (59.1+/-5.1 % vs. 200 nM orexin-A, n=8, and 67+/-3.8 % vs. 200 nM orexin-B, n=12, respectively). The PKC inhibitor chelerythrine (10 and 100 mu M) significantly decreased the orexin-A (200 nM)-induced [Ca2+](l) increase (59.4+/-4.8 % P<0.01, n=10 and 4.9+/-1.6 /0, P<0.01, n=9) versus response to orexin-A). It was also found that chelerythrine dose-dependently inhibited the [Ca2+](1) response to 200 nM orexin-B. In conclusion, our results suggest that orexins activate intracellular calcium signaling in cultured rat sensory neurons through PKC-dependent pathway, which may have important implications for nociceptive modulation and pain.
Keywords: Orexin A; Protein Kinase C; Calcium signaling; Nociception; Sensory neuron